Medieval Canonists and their contribution to the contemporary constitution theory - MORÁN GARCÍA, GLORIA M. (Prawo Kanoniczne, 2017)
The contribution of medieval canon lawyers regarding to the development of the legal bases of contemporary constitutional thinking is analyzed in three areas: 1) Origin and development of the principle of sovereignty, from the concepts of jurisdictio and potestas. Papal sovereignty and its limits, from the doctrine of plenitudo potestatis. 2) Relationship between individual and collegiate power from the legal abstractions of universitas and persona representata. 3) Their contribution to the consensus theory of power and doctrinal development of the concept congregatio fidelium.